The National Days in the Bilingual School - Idit Perelmuter, Idit Perelmuter (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Idit Perelmuter, The National Days in the Bilingual School. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 299–333. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.14 The bilingual school tends to address both the national days of the Arabs and the national days of the Jews as a part of its multicultural perception. As aforementioned, these days are characterized as tense and complicated days in the school, both for the Arabs and for the Jews, because of the narratives and perceptions that they represent, which sometimes are contradictory and. Nevertheless, it is possible to see that the school addresses the different perceptions and narratives of each culture, with recognition of the difference and uniqueness of each one of them and with reinforcement of the commonalities between them. In this way, it gives hope and encourages the desire for a shared life between Jews and Arabs in Israel, which on the one hand includes the difference and on the other hand broadens the common denominator between the two groups. This article will describe the national days of Arabs and Jews in the bilingual school in Jerusalem. It will focus on the meaning of the days, their complexity, and the ways of coping and implementation in the framework of the school, with reference to the school perception.